2018
DOI: 10.5539/jas.v10n3p244
|View full text |Cite
|
Sign up to set email alerts
|

Bromatological Analysis, Chemical Composition and Bioassays from the Genipa americana L. (Rubiaceae)

Abstract: Genipa americana L. well known as genipap, is a tree that is widely distributed throughout the Brazilian territory. The communities appreciate the genipap fruits, since they are used as food; in addition to that, their fruits have numerous seeds that can be used in the production of vegetable oil. This being, in this work inclined to a bromatological study of the genipap fruits and chemical composition and bioassays from vegetable oil seeds. Obtaining the highest percentage of lipids in the seeds that was of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…63 Ávila et al carried out the fatty acid prole of the G. Americana seed oil and reported that linoleic acid was the main acidic component in the biomass, with a percentage of 61.5%. 64 The results in this study indicate that the extracted and dried genipap oil contains 55.4 ± 2.4 wt% genipin. Moreover, 1 H-NMR analysis allowed us to accurately estimate the amount of genipin contained in the genipap oil (Fig.…”
Section: Chemical Characterization Of the Oilmentioning
confidence: 61%
See 1 more Smart Citation
“…63 Ávila et al carried out the fatty acid prole of the G. Americana seed oil and reported that linoleic acid was the main acidic component in the biomass, with a percentage of 61.5%. 64 The results in this study indicate that the extracted and dried genipap oil contains 55.4 ± 2.4 wt% genipin. Moreover, 1 H-NMR analysis allowed us to accurately estimate the amount of genipin contained in the genipap oil (Fig.…”
Section: Chemical Characterization Of the Oilmentioning
confidence: 61%
“…63 Ávila et al carried out the fatty acid profile of the G. Americana seed oil and reported that linoleic acid was the main acidic component in the biomass, with a percentage of 61.5%. 64…”
Section: Resultsmentioning
confidence: 99%
“…Then, the collected fruits were taken to the Laboratory of the Agronomic Research Center, at the Agricultural Sciences Center, Cauamé campus, Federal University of Roraima, fruits with good appearance were selected, washed previously with distilled water and then with hypochlorite solution of sodium chloride and finally with distilled water again according to the procedure described [7]. Table 1 -Names and families of fruits cultivated in the Northern Amazon studied in this work.…”
Section: Preparation Of Samplesmentioning
confidence: 99%
“…Then, the collected fruits were taken to the Laboratory of the Agronomic Research Center, at the Agricultural Sciences Center, Cauamé campus, Federal University of Roraima, fruits with good appearance were selected, washed previously with distilled water and then with hypochlorite solution of sodium chloride and finally with distilled water again according to the procedure described [7]. The fruits were pulped, weighed and frozen in an ultra-freezer at -80 o C for further lyophilization in Liotop L101 lyophilizer for 48 hours, until complete drying.…”
Section: Preparation Of Samplesmentioning
confidence: 99%